Analisis Kinerja Petugas Lapangan Keluarga Berencana Terhadap Partisipasi Masyarakat dalam Program KB di Kabupaten Enrekang - Marthen Ismail (PRAJA: Jurnal Ilmiah Pemerintahan, 2019)
Abstract The goal of this research is to determine how the field officers’ performance affect peoples’ participation on family plannings program (what we call “Keluarga Berencana”) in Enrekang regency, along with all influencing factors. This research’s type is quantitative research using descriptive approach to describe the field officers’ performance within people’s participation on family plannings program in Enrekang regency along with all influencing factors. The methods used to collect data were observation, interview with chosen respondents using questionnaires. The populations were all Enrekang’s people accepting the program (family plannings program acceptors). Then they were sampled by using cluster/area sampling method, resulting nine (9) people from each twelve (12) districts in Enrekang regency. The final result from this research concluded that the performance of family plannings program field officers (we call it PLKB) within people’s participation in Enrekang regency was inside very good category by scoring 4,38.